2018
DOI: 10.1371/journal.pone.0195499
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing adherence in HIV prevention product trials: Development and psychometric evaluation of simple tools for screening and adherence counseling

Abstract: BackgroundLow adherence in recent HIV prevention clinical trials highlights the need to better understand, measure, and support product use within clinical trials. Conventional self-reported adherence instruments within HIV prevention trials, often relying on single-item questions, have proven ineffective. While objective adherence measures are desirable, none currently exist that apply to both active and placebo arms. Scales are composed of multiple items in the form of questions or statements that, when comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…Further research could be beneficial to refine item content. Nevertheless, the correlations between all of the subscales were consistent with our original assumptions based on the literature [ 9 ], providing evidence for their construct validity. An additional limitation is that our tools (both the original vaginal ring and oral PrEP scales) were developed and validated among young adult African women from South Africa and Kenya.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Further research could be beneficial to refine item content. Nevertheless, the correlations between all of the subscales were consistent with our original assumptions based on the literature [ 9 ], providing evidence for their construct validity. An additional limitation is that our tools (both the original vaginal ring and oral PrEP scales) were developed and validated among young adult African women from South Africa and Kenya.…”
Section: Discussionsupporting
confidence: 85%
“…As PrEP and other HIV prevention products become more widely available, product adherence poses a serious challenge to their successful use, particularly among young African women [ 6 , 8 , 9 ]. In trials of PrEP effectiveness, sub-analyses indicated that poor adherence to the prescribed dosing regimen reduced effectiveness [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, parents’ behaviours of adherence were self-reported. Although self-reported adherence has demonstrated adequate validity [34], reported levels are the respondents’ perception of their adherence, and are not necessarily a true reflection of actual events. It is therefore possible that our results represent an overly optimistic view of the extent of adherence to HEP.…”
Section: Discussionmentioning
confidence: 99%